Assisted Reproductive Technologies: Impact on Parenthood Law - Kovaček Stanić, Gordana (European Integration Studies, 2025)
This study analyses changes in parenthood law as a consequence of using assisted reproductive technologies (ART) for bearing a child, particularly focusing on the following treatments: ova donation, surrogate motherhood, homologous artificial insemination, heterologous artificial insemination (artificial insemination by donor), posthumous fertilisation, and embryo donation. The study examines Serbian legal solutions and court practice, as well as comparative solutions and relevant decisions of the European Court for Human Rights. It primarily aims to determine the legal grounds for establishing motherhood and fatherhood in the cases using ART and examine the issue of legal status and rights of the donor of the genetic material.